The effect of alcohol use disorder symptom and recovery narratives on problem-recognition: A randomized online trial. (November 2022) - Leonhard, Anya; Leonhard, Christoph; Sander, Christian; Schomerus, Georg
Highlights: Continuous vs dichotomous alcohol use disorder symptom narratives and abstinence vs nonabstinence recovery narratives can be conceptualized as separate variables. Non-abstinence recovery narratives alone boost continuum beliefs of alcohol use disorder. An interaction effect between continuum symptom and non-abstinence recovery narratives increases self-recognition of risky drinking. Abstract: Background: Low problem recognition is a barrier to seeking treatment for alcohol use disorder ("AUD"). Promoting continuum belief narratives, which conceptualize AUD as a spectrum, together with narratives that promote non-abstinence recovery may boost self-recognition of risky drinking. This experimental study examines the effect of dichotomous vs continuous symptom narratives and non-abstinence vs abstinence recovery narratives on self-recognition of risky drinking among students. Methods: N = 489 participants were randomized to one of four interventions combining a continuous vs dichotomous AUD symptom narrative with an abstinence vs moderated drinking AUD recovery narrative in a 2×2 design. Participants completed demographic and alcohol use (AUDIT-C) preintervention measures and postintervention measures assessing self-recognition of risky drinking and endorsement of continuum beliefs. Results: Moderate drinking recovery narratives resulted in higher endorsement of continuum beliefs (F (1, 485) = 16.27, p <.001, η 2 p =.032 90 % CI [0.01, 0.06]). Recognizing own risky drinking behavior was unaffected by the interventions. However, in a subgroup of participants without prior AUD experience who met AUDIT-C criteria for risky drinking, the combination of a continuous symptom narrative and moderated drinking recovery narrative resulted in higher problem recognition (F (1, 48) = 5.79, p =.020, η 2 p =.10, 90 % CI [0.01, 0.25]). Conclusions: Exposure to moderated drinking recovery narratives may help develop an awareness in young adults that problematic alcohol use exists on a spectrum. Among those at increased risk for AUD, exposure to narratives that promote a continuous model of AUD and non-abstinence recovery may increase problem recognition.